THE DIRECT AND INDIRECT COST OF HEPATITIS B AND C VIRUS REALTED DISEASES: EVIDENCE FROM PAKISTAN (The Research of Medical Science Review, 2024)
Health is the key and significant asset that a human being has that allow people to exclusively develop their abilities. If this asset corrodes or not fully developed, it will cause emotional and physical weakness that causes hindrances in people lives. Keeping in view the importance of health in human capital and human development index, it is important to conduct a study that highlight the consequence of Hepatitis in Pakistan. This study is designed to estimate the effect of viral hepatitis (B & C) on labor productivity, family income, morbidity and mortality, estimate the direct and indirect cost hepatitis (B & C) and total cost imposed on each patient and their family in Pakistan. Primary data was collected from 8,388 Hepatitis B and C patients at district headquarter hospitals, private hospitals and doctors’ clinic from 77 districts across Pakistan including Azad Jammu and Kashmir and Gilgit Baltistan through a well design questioner containing 36 questions based on demographic and economic indicators. Descriptive, inferential statistical tools and probit logit and OLS econometric techniques were applied for data analysis. This study also originated significant direct relationship between total per month direct medical cost and indirect medical cost at different disease stage. Higher direct medical costs and indirect medical costs were found with advanced disease and vice versa. In the initial stage of the disease most of the direct medical costs were associated with diagnostic charges and medical services whereas the decompensated cirrhosis stage a large portion of direct medical costs were related to hospital admission and medication. Average per patient expenditure for Hepatitis B patients were estimated at Rs. 23,505 (150.65 $) per month while for hepatitis C patients it was estimated Rs. 23,779 (152.41 $) with average per patient expenditure of Rs. 16,162.5 (103.47$) and Rs.7479.5 (47.93 $) per month. The results also showed a slight difference in the average per month health care expenditure of Hepatitis B and C patients whereas the difference in direct and indirect cost of hepatitis B and C were moderate and recorded Rs. 15,430 (98.9 $), Rs. 8,075 (51.75 $) and Rs.8,075 (51.75 $), Rs. 6,884 (44.12 $) respectively. Finally, the per patient cost of Hepatitis B and C were found and concluded Rs.23,462 (151.53 $) per month.